Rhabdomyolysis caused by exercise - Diana Avila - Reyes; Euclides José Cruz-Echeverry; David Ricardo Echeverry-Piedrahita; José Fernando Gómez-González; Mateo Aguirre-Flórez (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2022)
Introduction: rhabdomyolysis is a clinical and paraclinical syndrome characterized by the presence ofskeletal muscle necrosis that leads to the consequent release of intracellular muscle components witha variable clinical presentation and complications that put life at risk such as acute kidney injury. Methods: we present a case report of a patient with rhabdomyolysis with severe elevation of muscle enzymes and secondary acute kidney injury who was subsequently documented (initial Total CK189,000 u/L) after extreme physical activity (CrossFit), who developed multiple complications and theneed for support in the Intensive Care Unit (ICU) with satisfactory outcome. Results: Patient with kidney failure, receiving renal therapy with a favorable evolution and survival atdischarge from the intensive care unit of a third-level hospital in the city of Pereira, Risaralda, Colombia. Conclusions: Rhabdomyolysis is a clinical and paraclinical syndrome characterized by the presence ofskeletal muscle necrosis. The main cause is severe direct traumatic injury or crushes injuries; however,other conditions such as infections, intoxication, muscle ischemia, neuroleptic malignant syndrome, malignant hyperthermia, metabolic disorders, and genetic pathologies can also cause it, and particularly, extended rest, immobilization or strenuous exercise. The clinical presentation and complications are variable.